Báo cáo kết quả đón Đoàn Nghị sĩ trẻ Thanh niên Đảng Dân chủ Tự do (LDP) Nhật Bản thăm làm việc tại Việt Nam (Từ ngày 21 - 25/8/2017) (2017)
Báo cáo kết quả đón Đoàn Nghị sĩ trẻ Thanh niên Đảng Dân chủ Tự do (LDP) Nhật Bản thăm làm việc tại Việt Nam (Từ ngày 21 - 25/8/2017)